UTILIZATION OF OPTICAL METHODS IN VELOCITY MEASUREMENTS OF SOLID POLLUTANTS - ČERNECKÝ, Jozef; BRODNIANSKÁ, Zuzana (Trends in education, 2009)
The present contribution is concerned with specific posibilities of optical method utilization in monitoring of solid pollutants in the atmosphere. In the Environmental Technology study programme as well as other related study programmes specialized to environmental technology a strong accent is put on technical means of measurement and monitoring. The students will be acquainted with new, nonconventional measurement techniques as is laser Doppler anemometry and holographic interferometry. Both methods are taught in the following subjects: Technical Means of Measurement and Monitoring, Technology of Air Protection and Utilization of Lasers in Metrology and Energy Technology and Equipment.
Keywords: Holographic interferometry; laser Doppler anemometry; solid pollutants.